2015
DOI: 10.3758/s13423-015-0879-3
|View full text |Cite
|
Sign up to set email alerts
|

Time discounting and time preference in animals: A critical review

Abstract: Animals are an important model for studies of impulsivity and self-control. Many studies have made use of the intertemporal choice task, which pits small rewards available sooner against larger rewards available later (typically several seconds), repeated over many trials. Preference for the sooner reward is often taken to indicate impulsivity and/or a failure of self-control. This review shows that very little evidence supports this assumption; on the contrary, ostensible discounting behavior may reflect a bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 125 publications
5
109
0
Order By: Relevance
“…The reward system integrates across dimensions to generate abstract decision variables; that is, ones that are correlated with value (e.g. Barron et al, 2017; Blanchard et al, 2015; Fellows, 2006; Hayden, 2016; Hunt and Hayden, 2017; Raghuraman and Padoa-Schioppa, 2014; Strait et al, 2014; Suzuki et al, 2017). However, unlike the visual system, which has only one major input locus—the eyes—the reward system has many inputs.…”
Section: Untangling Information In Form Visionmentioning
confidence: 99%
“…The reward system integrates across dimensions to generate abstract decision variables; that is, ones that are correlated with value (e.g. Barron et al, 2017; Blanchard et al, 2015; Fellows, 2006; Hayden, 2016; Hunt and Hayden, 2017; Raghuraman and Padoa-Schioppa, 2014; Strait et al, 2014; Suzuki et al, 2017). However, unlike the visual system, which has only one major input locus—the eyes—the reward system has many inputs.…”
Section: Untangling Information In Form Visionmentioning
confidence: 99%
“…Another problem with the compensating delay discounting design is the assumption that the animals are affected by consequences following reward delivery (Hayden, 2016). In other words, it assumes that the animals are aware of a waiting time between trials.…”
Section: The Problematic Inter-trial-intervalmentioning
confidence: 99%
“…A possible explanation for this is an ecological one: In nature, the length of the inter-trial-interval is likely to correlate with the size of the reward, since the animal needs to consume and digest. The inter-trial-interval would not become shorter as LL grows larger (Hayden, 2016). We may use the analogy of hunting prey: An increased delay is analogous to increased hunting or searching time, which may secure a larger prey (LL reward).…”
Section: The Problematic Inter-trial-intervalmentioning
confidence: 99%
See 1 more Smart Citation
“…The field is characterized not only by the standard empirical debates, but also by elementary definitional debates about what is and is not self-control, and whether it is a single thing or multiple distinct things [2,3]. These issues, difficult enough to approach in human studies, loom even larger in animal studies, where we cannot directly talk to our subjects [4,5]. A new study by Beran and Hopkins, reported in this issue of Current Biology [6], makes a great stride by linking self-control to general intelligence in chimpanzees.…”
mentioning
confidence: 99%